2021
DOI: 10.3390/su13137206
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of CSR Attributes on CSR Authenticity: Focusing on Mediating Effects of Digital Transformation

Abstract: What corporate social responsibility (CSR) attributes determine the CSR authenticity of a company? In the face of the Fourth Industrial Revolution, what direction should the CSR strategy pursue? In the electronics industries in Korea and China, are there any differences in CSR attributes? In this study, we start with some of these basic questions. Considering the promotional and actual costs incurred from CSR activities, CSR strategy are not an issue that can be easily determined from the corporate perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 49 publications
2
28
0
1
Order By: Relevance
“…Verina and Titko (2019) proposed that companies undergo "organizational change" and "cultural transformation" and find "ways to move towards customer centricity" in the context of DT. Moreover, DT is a strong partial mediator between CSR attributes and CSR authenticity (Liu and Jung, 2021). In addition, Camodeca and Almici (2021) found that digital technologies significantly improve ESG and help companies to achieve Sustainability Development Goals.…”
Section: Dt and Cemmentioning
confidence: 97%
“…Verina and Titko (2019) proposed that companies undergo "organizational change" and "cultural transformation" and find "ways to move towards customer centricity" in the context of DT. Moreover, DT is a strong partial mediator between CSR attributes and CSR authenticity (Liu and Jung, 2021). In addition, Camodeca and Almici (2021) found that digital technologies significantly improve ESG and help companies to achieve Sustainability Development Goals.…”
Section: Dt and Cemmentioning
confidence: 97%
“…Recent studies investigated the construct of authenticity in CSR with special regard to antecedents influencing its perception and ultimately the degree of perceived authenticity among consumers (Becker-Olsen et al, 2006;Alhouti et al, 2016;Joo et al, 2019;Jeon and An, 2019;Liu and Jung, 2021). The following table provides an overview of the antecedents of CSR authenticity (see Table 1).…”
Section: Theoretical Framework and Hypotheses 21 Research Modelmentioning
confidence: 99%
“…Investigated antecedents and definition Type and sample size Liu and Jung (2021) Sustainability CSR sustainability relates to keeping CSR activities consistent (systematically aligned with the overall firm's strategy) with an entity's resource commitment, objectives and performance tactics from start to finish continuously Fit CSR fit is a relational relationship between the attributes of the enterprise and the CSR activities it implements Impact CSR impact refers to the extent to which CSR activities have substantially resulted in the resolution of social problems…”
Section: Author and Yearmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides financial information, the influence of the enterprise digital information environment on the capital market is reflected in two aspects: the enterprise social responsibility report (Liu and Jung, 2021) and the non‐public information. The corporate social responsibility report's disclosure of non‐financial information plays a significant role in replenishing financial information (Porter and Kramer, 2006), which will effectively promote forecast accuracy and the number of analysts tracking it, and lower the degree of information asymmetry between the capital market and enterprise.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%